Optimization of degradable temporary plugging material and experimental study on stability of temporary plugging layer - Chen, Zhengrong; Wu, Guangai; Zhou, Jun; Ai, Chuanzhi; Zhang, Anshun; Xie, Xin; Wu, Jianshu; Kong, Xiangwei; Li, Song (Frontiers in Physics, 2023)
Temporary plugging technology is an important drilling technique for maintaining wellbore stability and resolving lost circulation problems. The key to its success lies in the use of materials that can form a tight and stable "temporary plugging layer" with certain pressure bearing capacity and a permeability close to zero in the loss channel near the wellbore. Experimental studies have been conducted to develop adhesion formulations for optimal temporary plugging materials, as the matching relationship between particle size and fracture width is critical ((0.5-1) / 1). By measuring the permeability of temporary plugging layer under varying confining pressure with a soap foam flowmeter, researchers have been able to evaluate the effectiveness, degradation, and dosages of temporary plugging agents. It has been shown that a single-particle material, such as a walnut shell, has a smaller permeability than a hyperfine CaCO3 coated temporary plug layer. The latter, however, is less capable of bearing pressure. By combining different materials, such as walnut shells and hyperfine CaCO3 particles, the researchers were able to create a temporary plug layer that had the lowest permeability and did not change much at variable confining pressures. Its pressure-bearing capacity is strong and the temporary plug works well. Experiments have shown that a ratio of 2:1 to 3:1 of hyperfine CaCO3 and walnut shell particles works well for plugging a fracture system with particles of size 2 to 3 times the fracture width. It developed an evaluation method for temporary plugging agents, studied their plugging capability and degradation performance for reservoir conversion, and evaluated degradation performance after successful temporary plugging. The temporary plugging rate of the temporary plugging agent increased from 98.10% to 99.81%, and the maximum temporary plugging pressure is 50.39 MPa, which can be completely reduced at 150 °C for 4 hours, meeting the technical requirements of "dense temporary plugging, two-way pressure bearing" to some extent.